Trastuzumab deruxtecan in HER2-positive advanced breast cancer with or without brain metastases: a phase 3b/4 trial - Harbeck, Nadia; Ciruelos, Eva; Jerusalem, Guy; Müller, Volkmar; Niikura, Naoki; Viale, Giuseppe; Bartsch, Rupert; Kurzeder, Christian; Higgins, Michaela J.; Connolly, Roisin M.; Baron-Hay, Sally; Gión, María; et al. (Nature medicine, 2024)
Trastuzumab deruxtecan (T-DXd) intracranial activity has been observed in small or retrospective patient cohorts with human epidermal growth factor receptor 2-positive (HER2+) advanced/metastatic breast cancer (mBC) and stable or active (untreated/previously treated and progressing) brain metastases (BMs). The phase 3b/4 DESTINY-Breast12 study investigated T-DXd in patients with HER2+ mBC and is, to our knowledge, the largest prospective study of T-DXd in patients with BMs in this setting. Patients (stable/active BMs (n = 263) and no BMs (n = 241)) treated with one or more prior anti-HER2-based regimens received T-DXd (5.4 mg per kg). Primary endpoints were progression-free survival (PFS; BMs cohort) and objective response rate (ORR) per Response Evaluation Criteria in Solid Tumors version 1.1 (non-BMs cohort). Additional endpoints included central nervous system (CNS) PFS, ORR, time to second progression, CNS ORR (BMs cohort), incidence of new symptomatic CNS metastases (non-BMs cohort), time to progression, duration of response, overall survival and safety (both cohorts). No formal hypothesis testing was conducted for this single-arm, open-label study. In the BMs cohort, 12-month PFS was 61.6% (95% confidence interval (CI): 54.9-67.6), and 12-month CNS PFS was 58.9% (95% CI: 51.9-65.3). In the non-BMs cohort, ORR was 62.7% (95% CI: 56.5-68.8). Grade 3 or higher adverse events occurred in 51% (BMs cohort) and 49% (non-BMs cohort) of patients. Investigator-reported interstitial lung disease/pneumonitis occurred in 16% (grade ≥3: 3%) of patients with BMs and 13% (grade ≥3: 1%) of patients without BMs. These data show substantial and durable overall and intracranial activity for T-DXd, supporting its use in previously treated patients with HER2+ mBC irrespective of stable/active baseline BMs. ClinicalTrials.gov identifier: NCT04739761.